Exploring Tensions in the Lives of Professors of Teacher Education: A Canadian Context - Sal J Badali (University of Windsor, 2011)
This article explores the major satisfactions and frustrations of professors of teacher education from faculties of education in Western Canadian universities. Data were collected in semi-structured interviews with 31 professors of various ranks. The purpose of the study weas to explore the manner in which these teacher educators frame their professional experiences and construct their roles within complex institutional contexts. The findings indicate that although professors view their work as highly positive, there are significant observable tensions in the professional lives. Two major themes characterizing the work of professors discussed: 1) satisfactions (working with students; delight in teaching; and fulfillment in research writing and scholarship), and 2) frustration (workload and time press issues; research and scholarship). Overall, results indicate a number of issues: many of the same things that gave them satisfaction as K-12 teachers give them satisfaction as professors; workloads and expectations are increasing; and professors acknowledge the centrality of scholarship as it relates to teaching.